Analisis Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Karyawan pada Gojek Tokopedia (GoTo) Logistics - Yuliga Narya, Nur; Waluya, Sri; Sianturi, Murdan (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2024)
Employee performance in an organization or company is the answer to the success or failure of the organizational goals that have been set. Bosses often don't pay attention to their employees' performance, unless things are really bad or things are going wrong. Too often managers or superiors do not know how bad the performance of employees who have fallen has caused the company or organization to face a serious crisis. Performance is a condition that must be known and confirmed to certain parties to determine the level of achievement of a company's results related to the vision carried out by a company and to know the positive and negative impacts of operational policies. The purpose of this study was to find out whether Leadership Style and Work Environment Affect Employee Performance at Gojek Tokopedia (GoTo) Logistics. And this research also aims to analyze the factors that have the most dominant influence on employee performance in the company. The population used in this research are employees who work at Gojek Tokopedia (GoTo) Logistics. The sample in this study was 50 employees who worked at Gojek Tokopedia (GoTo) Logistics. Data collection techniques use primary data and questionnaires. The data analysis method used is in the form of validity and reliability tests, classical assumption tests, multiple linear regression analysis, T-test and F-test and the coefficient of determination (R2). From the results of the analysis, the indicators in this research are valid and the variables are valid. The results of the T (Partial) test can be seen that the significant value of the leadership style variable (X1) is 0.000 <0.05 and the t count value is 13.237 > T table 1.705. Work environment variable (X2) is 0.071 > 0.05 T count 1.845 > T table. And the F Test Results (Simultaneous) produced an F hit of 145.444 with a sig value of 0.000 < 0.05. This value explains that the calculated F value > F table is 145.444 > 3.183 so it can be concluded that this proves that there is a simultaneous effect. And the most dominant factor influencing employee performance is the Leadership Style variable. This can be seen from the results of multiple linear regression analysis Y = 0606 + 0.828 X1 + 0.158 X2. This research is expected to provide benefits for companies to be able to improve leadership styles and improve the work environment as expected by employees, so that employee performance at the company can increase.